Use of Vaginal Packing in the Management of Lower Uterine Segment Atony - Bagli, Ihsan; Erdem, Selami (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVES: We aimed to evaluate the effect of vaginal packing in the management of lower uterine segment atony that it is a distinct cause of primary postpartum hemorrhage. We also set out to determine the incidence of lower uterine segment atony. STUDY DESIGN: This is a retrospective study involving 967 births out of 25 000 deliveries in one institution in the year 2018. Of 967 births were managed by the corresponding author of this study. Of 14 lower uterine segment atony patients were occurred during the study period among 967 deliveries. All patients with lower uterine segment atony were treated by vaginal packing. RESULTS: The occurrence of postpartum hemorrhage among the study population was 57/967 (5.9%). We found the incidence of lower uterine segment atony to be 1.4% (14/967). Vaginal packing as a first attempt was found to be successful for controlling hemorrhage in 13/14 (92.8%) patients with lower uterine segment atony. It was found to occur in the repeated cesarean group more than other groups, but this difference was not statistically significant (p=0.157). Any complications were occurred related to packing. CONCLUSION: Vaginal packing was found to be simple, safe, and feasible in terms of achieving hemostasis in cases of postpartum hemorrhage due to lower uterine segment atony. Vaginal packing is a potential method for preserving the uterus before further surgical application.